Carer levels of concern on driving and other activities in older people that put others at risk. (13th May 2013) - Helmes, Edward; Pachana, Nancy A.
<x xml:space="preserve">Abstract</x> Objectives Early signs of dementia may raise concerns in family members as to the safety of the affected person when engaged in common activities. Here we report on the relative frequency of such concerns using data from the three waves of the Canadian Study of Health and Aging (CSHA). Our focus is on driving, cooking and paying bills, with a prediction that most carers' concern would be over driving. Method Participants were 2780 Canadians over 65 years, who underwent the first wave of CSHA and were subsequently followed during the next two waves. Results As predicted, concerns about driving were relatively more common than concerns about cooking and handling finances (P = 0.021) in the cognitively intact group, with the opposite order observed in the group with dementia. Conclusion Carer concerns for those diagnosed with dementia shift with the progression of cognitive changes, with concerns declining over the 10‐year period.